(untitled) (Revista Contexto & Saúde, 2024)
Objective: To evaluate the level of functional capacity and its association with the quality of life (QoL) in patients with atypical parkinsonism (AP). Methods: This is a cross-sectional study involving a clinical assessment by a physician and a physiotherapist to confirm the diagnosis of AP and complete the clinical analysis; Timed Up and Go (TUG) test, handgrip strength, Parkinson’s Disease Quality of Life Questionnaire (PDQ-39), Hoehn & Yahr (H&Y) scale, Frontal Assessment Battery (FAB), and Montreal Cognitive Assessment (MoCA). Results: Twenty-one elderly patients with AP were recruited, with a predominance of males (76%). Functional impairment was observed in 80% of patients with a TUG > 20 seconds, and 57% had dynapenia. Stratifying patients with and without dynapenia, we found that those with dynapenia had worse QoL according to the PDQ-39 questionnaire (p = 0.04). Additionally, a significant negative correlation was found between the dynamometer values of the dominant limb (Kgf) and QoL in patients with AP (R = -0.449 and P = 0.049); a significant positive correlation was observed where the severity of AP assessed by the Hoehn & Yahr scale directly influenced functional capacity as measured by the TUG test (R = 0.580 and P = 0.009), and a significant correlation between MoCA and FAB (R = 0.867 and P = 0.001). These findings were supported by significant results in linear regression, which determined the direct influence of functionality on QoL in these patients. Conclusion: The severity of AP negatively impacts functionality, consequently impairing QoL in patients diagnosed with AP.